PERTANGGUNGJAWABAN NOTARIS ATAS KERUGIAN KLIEN AKIBAT KESALAHAN DIDALAM PENERBITAN AKTA - Parwati, Komang Ayu Dewi; Ratna Maharani, I Gusti Ayu Stefani (Kertha Negara : Journal Ilmu Hukum; Vol 12 No 8 (2024), 2025)
The goal of this study is to identify and evaluate the types of mistakes notaries make when issuing deeds that could endanger their clients. It also examines the steps a notary must take in accordance with Indonesian law to establish liability in the event that a mistake is proven to have caused harm to a client during the issuing process. This study employs normative research techniques together with a legal concept analysis and statutory methodology. The initial finding of this study is that notarial mistakes can take many different forms, including typographical problems in notarial copies, flaws in notarial deed form, and errors in notarial deed content. In addition, notarial errors in the issuance of deeds can also be classified into 3 (three) main categories, namely administrative errors, procedural errors, and substantive errors. Second, that the liability of a notary if proven to have made a mistake that harms the client in the issuance of a deed is divided into 3 (three) forms of responsibility, namely in terms of Civil Law, Administrative Law, and Criminal Law.